Interpersonal Self-Efficacy, Goals, and Problems of Persistently Depressed Outpatients: Prototypical Circumplex Profiles and Distinctive Subgroups. (December 2018) - Locke, Kenneth D.; Sayegh, Liliane; Weber, Charlotte; Turecki, Gustavo
Severely and persistently depressed outpatients ( n = 138) completed interpersonal circumplex measures of self-efficacy, problems, and values/goals. Compared with normative samples, patients showed deficits in agency: They reported less self-efficacy, especially for being assertive, tough, and influential; stronger goals, especially to avoid conflict or humiliation; and more problems, especially with being too timid, inhibited, and accommodating. Circular and structural summary indices suggested greater variability among patients in goal profiles than in efficacy or problem profiles; nonetheless, latent profile analyses identified coherent subgroups of patients with distinct patterns of efficacy (e.g., lacking confidence for speaking up vs. setting boundaries) and problems (e.g., being overly inhibited vs. self-sacrificing) as well as goals (e.g., to be included vs. unobtrusive). Women and those with more severe symptoms were overrepresented in the least agentic groups. The results show how observing patients through multiple circumplex surfaces simultaneously can help clarify their interpersonal dispositions and inform interventions.